1999
DOI: 10.1046/j.1365-3032.1999.00126.x
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variation in cold hardiness of eggs and neonate larvae of the yellow‐spotted longicorn beetle Psacothea hilaris

Abstract: Cold hardiness of eggs and neonate larvae of the yellow-spotted longicorn beetle, Psacothea hilaris (Pascoe) was examined using six geographical populations in Japan. Particular attention was paid to cold hardiness of eggs and neonate larvae of the subtropical population (Ishigaki), because the east Japan populations are considered to have been introduced from a subtropical area, and the overwintering stage in the east Japan populations is incidentally shifted from the original mature larval stage to the egg o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 13 publications
(19 reference statements)
1
16
0
Order By: Relevance
“…There are also some genetic differences among locust populations from south to north in China (Zhang & Kang, 2000), but it is unknown whether such differences affect their cold hardiness. The geographic variations in cold hardiness of a single species or inter-population have also been supported strongly in previous studies (Turnock et al, 1990(Turnock et al, , 1998Shintani & Ishikawa, 1999;Kallushkov & Nedved, 2000), however a comprehensive study of locust cold hardiness and its relationship with geographical distribution has not been conducted.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…There are also some genetic differences among locust populations from south to north in China (Zhang & Kang, 2000), but it is unknown whether such differences affect their cold hardiness. The geographic variations in cold hardiness of a single species or inter-population have also been supported strongly in previous studies (Turnock et al, 1990(Turnock et al, , 1998Shintani & Ishikawa, 1999;Kallushkov & Nedved, 2000), however a comprehensive study of locust cold hardiness and its relationship with geographical distribution has not been conducted.…”
Section: Introductionsupporting
confidence: 56%
“…Leather et al (1993) also outlined the great influence on the population dynamics of some insect species of temporal and spatial variation in winter temperatures. Similarly, Shintani and Ishikawa (1999) considered cold hardiness of the yellow-spotted longicorn beetle Psacothea hilaris to be essential in assessing its potential to establish a population in east Japan.…”
Section: Introductionmentioning
confidence: 99%
“…In most parts of China, apart from the western high-plateaux, the sum of effective temperatures is high enough for the beetle development during the summer. Several researchers have reported that winter cold is one of the most important factors that limit the distribution of insects in the high-latitude zones [4,12,20,23]. We suggest that low temperatures in winter also play an important role in limiting the distribution and dispersal range of the beetle in China.…”
Section: Introductionmentioning
confidence: 70%
“…Within the family of long-horned beetles, only the cold hardiness of eggs and neonatal larvae of the yellow-spotted longicorn beetle Psacothea hilaris have been studied in Japan [20]. Although several studies have been conducted on the biology of the Japanese pine sawyer and its vectoring nematode B. xylophilus [11,13,14], research on its cold tolerance is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The egg stage is the principal overwintering stage in many insects and other terrestrial arthropods, and considerable interest has been shown by entomologists in the cold resistance of eggs (SØmme, 1982(SØmme, , 2000Gehrken, 1989;Hanson & Craig, 1994;Block et al, 1995;Strathdee et al, 1995;Shintani & Ishikawa, 1999;Jing & Kang, 2003). Cold hardiness is defined as the capacity of a species to survive long or short term exposure to low temperature (Lee, 1991).…”
Section: Introductionmentioning
confidence: 99%